2021
DOI: 10.3390/ijms221910618
|View full text |Cite
|
Sign up to set email alerts
|

The Function of SUMOylation and Its Critical Roles in Cardiovascular Diseases and Potential Clinical Implications

Abstract: Cardiovascular disease (CVD) is a common disease caused by many factors, including atherosclerosis, congenital heart disease, heart failure, and ischemic cardiomyopathy. CVD has been regarded as one of the most common diseases and has a severe impact on the life quality of patients. The main features of CVD include high morbidity and mortality, which seriously threaten human health. SUMO proteins covalently conjugate lysine residues with a large number of substrate proteins, and SUMOylation regulates the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 150 publications
(216 reference statements)
0
14
0
Order By: Relevance
“…UBC9 adds a SUMO group to GATA4 at K366, which activates particular gene expression in pluripotent cardiac cells. 1051 …”
Section: Sumoylationmentioning
confidence: 99%
“…UBC9 adds a SUMO group to GATA4 at K366, which activates particular gene expression in pluripotent cardiac cells. 1051 …”
Section: Sumoylationmentioning
confidence: 99%
“…Wang et al reported that SUMO1 deficiency can cause cardiac septal dysplasia and congenital heart disease [ 32 ]. SUMOylation of GATA4, GATA5, and GATA6 regulates cardiac value and expression [ 33 ]. SUMOylation of GATA4 activates the modification of SUMO-1 at K445 and regulates the expression of cardiac protein in cardiogenic genes [ 34 ].…”
Section: Ptms In Heart Developmentmentioning
confidence: 99%
“…Interestingly, SUMO1 knockout mice are survivable because SUMO2/3 can compensate for most functions of SUMO1 (Zhang et al, 2008;Wang et al, 2014a). SUMO1 and SUMO2/3 are common, while SUMO4 is only expressed in few organs, such as spleen and kidney (Du et al, 2021). SUMO4 is associated with the pathogenesis of type I diabetes mellitus.…”
Section: Sumo Proteinsmentioning
confidence: 99%